HPV 16-associated tumours: IL-12 can repair the absence of cytotoxic and proliferative responses of tumour infiltrating cells after chemotherapy - Indrová, Marie; Bieblová, Jana; Rossowska, Joana; Kuropka, Piotr; Pajtasz-Piasecka, Elzbieta; Bubeník, Jan; Reinis, Milan (International journal of oncology, 2009)
We have examined the effect of IL-12-producing cellular vaccines on the cytotoxicity and proliferative potential of CD45+ tumour-infiltrating cells (TIL) in mice carrying syngeneic TC-1 and TC-1/A9 HPV 16-associated tumours after chemotherapy with CBM-4A ifosfamide derivative. The chemotherapy resulted in the decrease of the CD4+ and CD8+ TIL, increase of the Gr-1+/CD11b+ TIL, no changes in the infiltration with CD4+/CD25+ Treg TIL, and decrease of the cytolytic and proliferative potential of the CD45+ TIL. Subsequent immunotherapy with the IL-12-producing, genetically modified TC-1 (TC-1-IL-12) cells increased tumour infiltration with CD8+ and CD4+ cells, decreased the Gr-1+/CD11b+ cells, and increased the cytolytic and proliferative potential of the CD45+ TIL. Taken together, these findings suggest that peritumoral administration of the IL-12-producing cellular vaccine can restore the cytolytic potential and inhibit immunosuppressive TIL-dependent mechanisms in the individuals bearing HPV 16-associated tumours, and explain our previously described tumour-inhibitory effects of the vaccine in mice with minimal residual disease after the tumour chemotherapy.
Keywords: Ifosfamide; Interleukin-12; Male; Lymphocytes, Tumor-Infiltrating; Cell Proliferation; infekce papilomavirem; Papillomavirus Infections; genetická terapie; ifosfamid; Neoplasms, Experimental; mužské pohlaví; CD8-Positive T-Lymphocytes; Flow Cytometry; Genetic Therapy; Human papillomavirus 16; cytotoxické testy imunologické; Immunotherapy; Cytotoxicity Tests, Immunologic; lidský papilomavirus 16; Angiogenesis Inhibitors; CD4-Positive T-Lymphocytes; průtoková cytometrie; Animals; lidé; CD8-pozitivní T-lymfocyty; experimentální nádory; Humans; inhibitory angiogeneze; zvířata; myši inbrední C57BL; imunoterapie; myši; nádorové buňky kultivované; Immunoenzyme Techniques; proliferace buněk; Mice, Inbred C57BL; Tumor Cells, Cultured; Mice; tumor infiltrující lymfocyty; imunoenzymatické techniky; interleukin-12; CD4-pozitivní T-lymfocyty